PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS PROBLEM BASED LEARNING PADA POKOK BAHASAN STRUKTUR ATOM - ', Fatmawati; ', Susilawati; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The objective of this research was to develop the student’s activity paper on the subject of Atomic Structure. The type of this research was research and development (R & D) with the 4-D development model which include Define, Design, Develop, and Disseminate. This research was to develop phase and be continue with a definite tryout. This research was conducted in FKIP Riau University. The data analysis technique used for this research was descriptive statistic. The descriptive analysis done by calculated the percentage of validation value. The average score of valuation to four expediency aspect of student’s activity sheet by validator’s team, such as the content properness, the language properness, course and the graphical has expediency value continued is 83,33%, 87,50%, 85,00%, and 84,375%. Thus, the average score totality of student’s activity paper based on the Problem Based Learning subject of Atomic structure is 85,05% which is in valid criteria, means that the LKPD Developed is proper to be use.Key Words: Student Activity Sheet, Problem Based Learning, and Atomic Structure